Internet Understanding Moderates the Influence of Technology Acceptance Model and Digital Taxation on Taxpayer Compliance - Sevendy, Tandy; Suhardjo, Suhardjo; Renaldo, Nicholas; Remy, Adrian; Meyer, Kaspar (First Ciera Publisher, 2023)
This study seeks to evaluate the influence of the Technology Acceptance Model and Digital Taxation on Tax Compliance, incorporating Internet Understanding as a moderating variable. The research employs multiple regression analysis and moderation calculations using the interaction method, with the Smart PLS application for processing questionnaire data. The sample consists of 194 individual taxpayers involved in businesses or independent work in Riau Province. The results indicate that the Technology Acceptance Model and Digital Taxation do not exert a significant impact on tax compliance. However, Internet Understanding demonstrates a substantial positive effect on Tax Compliance. Additionally, the moderation of Internet Understanding in relation to the Technology Acceptance Model and Digital Taxation significantly enhances their positive effects on Tax Compliance.